The Influence of Experiential Marketing, Electronic Word of Mouth, and Brand Image on Customer Loyalty for Everwhite Beauty Products - Situngkir, Ober; Nuvriasari, Audita (PT FORMOSA CENDEKIA GLOBAL, 2024)
This inquire about points to evaluate the impact of Experiential Marketing, Electronic Word of Mouth, and Brand Image on Client Dependability for Everwhite excellence items. The sampling technique used a questionnaire technique with the number of research samples was 100 respondents. Speculation test comes about demonstrate that Experiential Marketing, Electronic Word of Mouth, and Brand Image have a positive and critical impact on customer loyalty for Everwhite beauty products. These show that the stronger the Experiential Marketing, Electronic Word of Mouth, and Brand Image, the more client dependability for Everwhite beauty products will increase. The comes about of coefficient of assurance (r²) test gotten an r square coefficient (r²) esteem of 0.523, which suggests that Experiential Marketing, Electronic Word of Mouth, and Brand Image contribute to client dependability by 52.3%. Therefore, these there variables together will have a positive and noteworthy impact on client dependability for Everwhite magnificence items.